Dampak COVID-19 terhadap Keuntungan Usaha Kuliner Bakso di Kecamatan Baturaja Timur Kabupaten Ogan Komering Ulu - Tirani Lubis; Endang Lastinawati; Putri Ayu Ogari (KaliAgri Journal, 2026)
Agricultural extension workers play a vital role in supporting the development of farming systems throughtheir functions as facilitators, innovators, motivators, group mobilizers, and educators. The effective implementation of these roles is essential for enhancing the success of agricultural extension services at the farmer level. This study aimed to analyze the role of agricultural extension workers in corn (Zea mays L.) farming in Batumarta I Village, Lubuk Raja District, Ogan Komering Ulu Regency. A survey method was employed, and the research site was purposively selected. The respondents consisted of 45 corn farmers from three farmer groups. Data were collected through structured interviews using a questionnaire and analyzed descriptively using a Likert-scale scoring approach. The findings revealed that the overall role of agricultural extension workers was categorized as high, with an average score of 15.72. The roles as facilitators, motivators, and educators achieved scores of 17.35 (very high), 17.16 (very high), and 17.51 (very high), respectively. Meanwhile, the roles as innovators and group mobilizers obtained scores of 13.25 (moderate) and 13.34 (moderate), respectively. These findings indicate that agricultural extension workers have effectively facilitated farming activities, motivated farmers, and enhanced farmers' knowledge and capacity. However, strengthening their roles as innovators and group mobilizers is necessary to promote the adoption of agricultural innovations and improve the effectiveness of farmer group development